2010
DOI: 10.1186/1746-4269-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Small ruminant feed systems: perceptions and practices in the transitional zone of Ghana

Abstract: BackgroundAdequate feeding is essential to realizing the potential of small ruminants to alleviate poverty among smallholder farmers. This study was conducted in two villages in the Ejura-Sekyedumase District of Ghana and was motivated by farmers' non-adoption of modern feed technologies, but more importantly by the need to understand the small ruminant feed system considering farmers' different socio-economic backgrounds and how these relate to small ruminant performance. In this study, the feed system was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…These findings were consistent with those of Hamadou et al (2008) and Duku et al (2010) who indicated that most (peri-)urban livestock keepers respond to declining grazing areas by shifting from the traditionally extensive towards more intensive feeding practices. Land is the fundamental resource required for farming, and access and tenure are critical (IFAD 2008).…”
Section: Discussionsupporting
confidence: 92%
“…These findings were consistent with those of Hamadou et al (2008) and Duku et al (2010) who indicated that most (peri-)urban livestock keepers respond to declining grazing areas by shifting from the traditionally extensive towards more intensive feeding practices. Land is the fundamental resource required for farming, and access and tenure are critical (IFAD 2008).…”
Section: Discussionsupporting
confidence: 92%
“…However, this study failed to quantify the salience of these examples of criteria given by local farmers, unlike this study. Duku et al [ 70 ] stated that smallholder farmers ranked their feed sources for small ruminants based on a multiplicity of reasons such as their availability, palatability, proximity, abundance, reliability and health risks in the transitional zone of Ghana. However, this study and others failed to quantify the salience of valuation criteria of locally available forage species.…”
Section: Resultsmentioning
confidence: 99%
“…But paradoxically livestock farms and animal numbers in the periurban areas of the region have been rising rapidly along with the urbanization of these areas, causing a shrinkage of grazing areas and a depletion of feed resources (Coulibaly et al, 2007;Ly et al, 2010). Feed scarcity has become the major constraint in the periurban ruminant production systems (Coulibaly 2008;Hamadou et al 2008;Duku et al, 2010) and as a response, herders have developed various coping strategies (Hamadou et al, 2008;Duku et al, 2010;Amadou et al, 2012). Despite its importance, cattle production in and around the major and secondary cities in southern Benin has received very little attention from research, development and policy.…”
Section: Introductionmentioning
confidence: 98%